School crime policy changes: The impact of recent highly-publicized school crimes - Snell, Clete (American journal of criminal justice, 2002)
Highly-publicized school shootings have heightened concern over school safety. This study examines the impact of school crimes on campus policy. The administrators of 336 Texas middle and high schools were surveyed. Policy changes were related to parental complaints about school crime policies and administrator perceptions that students felt less safe. School administrators should base safety policies on strategies that have been evaluated for their effectiveness in reducing school crime and fear.